Physically abused children's emotion understanding of self and peers in the context of peer relationships - Go, Laarni K. (Animo Repository, 2017)
Emotion understanding is one of the key skills in emotional competence (Saarni, Campos, Camras, & Witherington, 2006; Denham, Warren, von Salisch, Benga, Chin, & Geangu, 2011, Saarni 2000), where it is composed of the ability of children to distinctly identify an emotion, share their own undertakings about emotions, retell situations that elicit emotions, show emotions to other people, and report their actions and feelings when an emotion is shown (Cassidy, Parke, Butkovsky & Braungart, 1992). However, emotion understanding had shown to have influenced by different factors, one of which is childrens early experiences. This study aimed to explore how physically abused children were able to understand their own and peers emotions that were happening in the context of their peer relationships. Using a multiple case study design, 12 physically abused children (9 are males and 3 are females) aged 9 to 12, underwent a semi-structured interview for approximately 60 to 90 minutes. There were two semistructured interview questionnaires that were used in this study: Interview of Emotion Understanding-Self (IEU-S) and Interview of Emotion Understanding-Peers (IEU-P). Together with 2 co-raters, data were analyzed thematically to identify the significant points that emerged from the interviews. Results showed that physically abused children were able to identify the emotions saya, lungkot, galit, takot, and hiya, and perceive the emotions masaya, malungkot, and galit from their peers. Participants were also able to express their emotions and perceive emotions from peers through explicit (e.g. verbal and physical expression) and implicit (e.g. keeping quiet and avoidance) expressions. Regardless of age, gender, and emotions, these participants expressed their emotions externally. Findings also showed reasons like play, relationship, and conflict as causes of their emotion experience and reasons like conflict and participants situation as causes of perceived peers emotion experience. Results further revealed that most of the participants did nothing when their peers showed their emotions but reported similarity to their peers emotion experience. Generally, these findings suggest that physically abused children in the study were able to respond to the questions about their emotions and even perceive their peers emotions.